Approximation of classes $C_∞ ^{\bar ψ }$ by zygmund sumsby zygmund sums - Fedorenko, An. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We consider the approximation of functions of the classes of $\bar ψ$ by Zygmund sums. In papticular, we present asymptotic equalities for the quantities $ε _n (C_∞ ^{\bar ψ } ;Z_n )_C$ under various conditions imposed on functions $ψ_1(·)$ and $ψ_2(·)$.